Corrosion protection by hydrophobic silica particle-polydimethylsiloxane composite coatings. (October 2015) - Ejenstam, Lina; Swerin, Agne; Pan, Jinshan; Claesson, Per M.
Graphical abstract: Highlights: Corrosion protection of steel substrates is achieved by a one-layer organic coating. Corrosion protection during almost 80 days of exposure to 3 wt% NaCl solution. The corrosion protective properties depend on particle concentration. Increase in diffusion path and hydrophobicity can explain the good properties. Abstract: In this study, the time-dependent corrosion protection ability of 10–15 μm thin polydimethylsiloxane-nanoparticle composite coatings was evaluated using mainly open circuit potential and electrochemical impedance spectroscopy measurements. The best result was obtained for the coating containing 20 wt% hydrophobic silica nanoparticles, where it was possible to achieve protection for almost 80 days in 3 wt% NaCl solution. The protective properties offered by this coating are suggested to be due to a synergistic effect of the hydrophobicity of the polydimethylsiloxane matrix and the prolonged diffusion path caused by addition of hydrophobic silica particles.